Dipturus argentinensis, argentine skate - Pollom, R. (2020)
The Argentine Skate (Dipturus argentinensis) occurs in the Southwest Atlantic from central Chubut to southern Santa Cruz, Argentina and off the northwest Falkland Islands (Malvinas). It inhabits continental and insular shelves and slopes at depths of 85–400 m. Maximum size is unknown as only immature specimens have been caught (up to 125 cm total length) and there is some question as to where the adult population occurs. This skate is captured in commercial demersal trawl fisheries, which are intense across its entire known geographic and bathymetric range. It is captured in the target trawl fishery for skates off the Falkland Islands (Malvinas). Identification is an issue, and it may be captured more than is perceived. More information is needed to determine the level of overlap with fisheries and this species' catchability and sensitivity to fishing. Research is needed on distribution, life history, population size and trends, and threats. Since it is unknown whether fishing is causing a population reduction, there is currently inadequate information available to assess the Argentine Skate beyond Data Deficient.